Simulation Study of Various Blade’s Numbers and Performance’s Effect Inside Impeller for Centrifugal Pump System - Zainal, Mohd Helmy Faidzhi; Mahmudin, Rahmah (Progress in Engineering Application and Technology, 2021)
One of the first pieces of powered machinery to be invented at the dawn of the industrial age was a crude form of pump. The pump has since evolved into an endless variety of types, sizes, and applications. This article will give an overview of the general types of pumps that are in common use in process plants. A functional understanding of pumps, their use, and application, is essential to understand how most processes are handled in process plants today. A pump is a device that moves fluids (liquids or gases), or sometimes slurries, by mechanical action, typically converted from electrical energy into hydraulic energy. Pumps can be classified into three major groups according to the method they use to move the fluid direct lift, displacement, and gravity pumps. Pumps operate by some mechanism (typically reciprocating or rotary), and consume energy to perform mechanical work moving the fluid. Pumps operate via many energy sources, including manual operation, electricity, engines, or wind power and come in many sizes from microscopic for use in medical applications to large industrial pumps. The research in this report is on simulations of radial backward impeller design. The 3 blades of impeller with 14 degree of inlet angle and 20 degree of outlet angle will be simulated and extracted with data on the pressure and velocity contained within.